Fluorine-19 Labeling of Stromal Vascular Fraction Cells for Clinical Imaging Applications. (28th October 2015) - Rose, Laura C.; Kadayakkara, Deepak K.; Wang, Guan; Bar-Shir, Amnon; Helfer, Brooke M.; O'Hanlon, Charles F.; Kraitchman, Dara L.; Rodriguez, Ricardo L.; Bulte, Jeff W.M.
Abstract : The location and persistence of stromal vascular fraction (SVF) cells, used clinically for various therapeutic targets, are important for determining treatment failure and success. The GID SVF-1 platform and a clinical protocol to harvest and label SVF cells with fluorinated ( 19 F) CS-1000 were successfully developed to track SVF cells with magnetic resonance imaging during radiation-induced fibrosis treatment in breast cancer patients. Abstract: : Stromal vascular fraction (SVF) cells are used clinically for various therapeutic targets. The location and persistence of engrafted SVF cells are important parameters for determining treatment failure versus success. We used the GID SVF-1 platform and a clinical protocol to harvest and label SVF cells with the fluorinated ( 19 F) agent CS-1000 as part of a first-in-human phase I trial (clinicaltrials.gov identifier NCT02035085) to track SVF cells with magnetic resonance imaging during treatment of radiation-induced fibrosis in breast cancer patients. Flow cytometry revealed that SVF cells consisted of 25.0% ± 15.8% CD45+, 24.6% ± 12.5% CD34+, and 7.5% ± 3.3% CD31+ cells, with 2.1 ± 0.7 × 10 5 cells per cubic centimeter of adipose tissue obtained. Fluorescent CS-1000 (CS-ATM DM Green) labeled 87.0% ± 13.5% of CD34+ progenitor cells compared with 47.8% ± 18.5% of hematopoietic CD45+ cells, with an average of 2.8 ± 2.0 × 10 12 19 F atoms per cell, determined using nuclear magnetic resonance spectroscopy. The vast majority (92.7% ± 5.0%) of CD31+ cells were also labeled, although most coexpressed CD34. Only 16% ± 22.3% of CD45−/CD31−/CD34− (triple-negative) cells were labeled with CS-ATM DM Green. After induction of cell death by either apoptosis or necrosis, >95% of 19 F was released from the cells, indicating that fluorine retention can be used as a surrogate marker for cell survival. Labeled-SVF cells engrafted in a silicone breast phantom could be visualized with a clinical 3-Tesla magnetic resonance imaging scanner at a sensitivity of approximately 2 × 10 6 cells at a depth of 5 mm. The current protocol can be used to image transplanted SVF cells at clinically relevant cell concentrations in patients. Significance: Stromal vascular fraction (SVF) cells harvested from adipose tissue offer great promise in regenerative medicine, but methods to track such cell therapies are needed to ensure correct administration and monitor survival. A clinical protocol was developed to harvest and label SVF cells with the fluorinated ( 19 F) agent CS-1000, allowing cells to be tracked with 19 F magnetic resonance imaging (MRI). Flow cytometry evaluation revealed heterogeneous 19 F uptake in SVF cells, confirming the need for careful characterization. The proposed protocol resulted in sufficient 19 F uptake to allow imaging using a clinical MRI scanner with point-of-care processing.